Foresight: Global competition for health care workers from Africa - Steffen Angenendt; Anne Koch; Melanie Müller (Stiftung Wissenschaft und Politik (SWP), 2020)
Pretoria, 12 February 2024: During a ceremony, the German Minister of Health and his South African counterpart sign the "Together We Care" agreement on the training and assignment to Germany of 20,000 South African nurses. 'Together We Care' is part of a comprehensive cooperation agreement. Training centres for medical personnel are to be set up in several South African cities. The agreement also contains commitments to support a vocational training system and the facilitation of visas. The event has received extensive media coverage and a predominantly positive reception. The German weekly newspaper FAZ publishes a front page article with the headline "Germany can hold its own in global competition", and the weekly taz welcomes the agreement with an article entitled 'Germany remains a country of immigration'.
Keywords: 320